Next-Generation Dental Materials: Exploring Bacterial Biofilm Formation on 3D-Printable Resin-Based Composites - Emerson Koji Uehara; Gustavo Castro de Lima; Janaina de Cassia Orlandi Sardi; Luciene Cristina de Figueiredo; Jamil Awad Shibli; Thabet Asbi; Doron Haim; José Augusto Rodrigues (Journal of Functional Biomaterials)
This study evaluated the microbial growth profile of subgingival multispecies biofilm on 3D-printable resin-based composites (PRBCs). A 96-well cell plate cultivated a 39-species biofilm associated with periodontitis over 7 days. Cylindrical specimens with 12 mm high and 3 mm diameters were prepared by the PRBC group (Cosmos Temp-Yller; Prizma 3D Bio Crown; Prizma 3D Bio Prov) and an acrylic resin as control. Further, these specimens were immersed in the well plate to allow biofilm formation. After growing for 7 days, the metabolic biofilm activity was evaluated by colorimetric assay and the microbial profile by DNA-DNA hybridization. Kruskal–Wallis and Mann–Whitney tests evaluated each bacteria count and complex group. A greater biofilm formation was observed on PRBC groups than on acrylic resin. The microbiological profile of PRBC was associated with a less pathogenic biofilm, with an absence of a red complex. Acrylic resin showed low biofilm growth, but the biofilm profile was related to periodontal disease, characterized by red-complex bacteria. The selection of PRBC may contribute more effectively to maintaining periodontal health than acrylic resin.